Complexity of interruptions: Evidence supporting a non‐interruption‐based theory. Issue 6 (22nd June 2020) - Brazzolotto, Paul; Michael, George A.
Abstract : Interruptions are known to be pervasive and harmful for concentration. It is also known that many factors can influence their effect, such as the complexity of the interrupting task. Less, however, is known about the processes underlying the resumption of the primary task, especially if the interrupting task is complex. Many hypotheses have been proposed but, as yet, it has not been possible to distinguish between their various qualities. In the current study, we carried out two experiments in which we manipulated the complexity of the interrupting task (either simple or complex) and the time between the end of the interrupting task and the resumption of the primary task (i.e., a break). Results showed that complex interrupting tasks led to longer resumption lags (RL) when there was no break, as has already been shown many times. However, while RL after simple interrupting tasks did not change as the break before resumption lengthened up to 1, 500 ms, those after complex interrupting tasks decreased. Moreover, after a break of 3, 000 ms, RL were longer overall. These results can only support the hypothesis based on task‐switching theories, but not hypotheses derived from interruption‐based models. Our findings therefore provide empirical evidence in support of explanations of complexity effects and the implications for research and application are discussed.